ANALISIS ISI SENSASIONALISME BERITA KRIMINAL (STUDI KASUS PROGRAM INEWS DAN KOMPAS SULSEL) - Mitha Mayestika Kuen; Yuweni Puji Saputri (Jurnal Ilmiah Pranata Edu, 2019)
ABSTRACTThis study discusses the Analysis of the Content of Sensationalism in Criminal News (Case Study of the Inews Program of South Sulawesi and KompasSulsel). The basis of this research began because of the fierce competition between television, newspapers and radio and the limitations of the medium, making television shift from the emphasis on public conversation leading to entertainment. There was a tight competition in the Market News. This condition provides an increase in a phenomenon called "sensationalism". Criminal news is classified into sensational news because the topics and images displayed include sensationalism. In addition, criminal news also has the ability to attract the attention of the public. This study aims to compare the level of sensationalism in news programs, especially criminal news on InewsTv and KompasTv, through the InewsSulsel and KompasSulsel programs. From these comparisons, the research method used is content analysis by comparing messages from different sources. This can be seen in the news of Inews-Sulsel and Kompas-Sulsel which are packaged with the selection of certain words in the title, the use of graphics, interesting drawings and information, the borrowing of expert mouths to convey ideas, angle setting for media presentation, music use, songs and repetitive effects so that they are familiar and determine the agenda agenda [agenda setting]. The results showed that the Inews-sulsel news program was more sensational in presenting news about the chaotic case of the Kingdom of Gowa compared to the Kompas-sulsel program. Keywords: Analysi; Sensationalism; Criminal News; Television News